2020
DOI: 10.1093/cercor/bhaa351
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Neuro-Immune-Vascular Plexus in the Ventricular Zone of the Prenatal Rat Neocortex

Abstract: Microglial cells make extensive contacts with neural precursor cells (NPCs) and affiliate with vasculature in the developing cerebral cortex. But how vasculature contributes to cortical histogenesis is not yet fully understood. To better understand functional roles of developing vasculature in the embryonic rat cerebral cortex, we investigated the temporal and spatial relationships between vessels, microglia, and NPCs in the ventricular zone. Our results show that endothelial cells in developing cortical vesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 87 publications
0
16
0
Order By: Relevance
“…Microglia–vascular interactions are present in the brain from early development into adulthood, through which microglia regulate blood–brain barrier (BBB) permeability, leukocyte extravasation, and angiogenesis ( Dudvarski Stankovic et al, 2016 ; Jolivel et al, 2015 ; Lou et al, 2016 ). In fact, microglia and microglial processes are closely associated with developing blood vessels in the neuroepithelium or in the ventricular zone, while Pu.1 −/− mice or Csf1 op/op mice that lack microglia and macrophages display impaired angiogenesis in the retina ( Arnold and Betsholtz, 2013 ; Dixon et al, 2021 ; Dudvarski Stankovic et al, 2016 ; Penna et al, 2021 ). In the adult brain, CD206-positive perivascular macrophages (PVMs) remain closely associated with blood vessels, while CD206-negative microglial cell bodies occupy the brain parenchyma isolated by the glia limitans ( Goldmann et al, 2016 ; Kida et al, 1993 ; Ransohoff and Engelhardt, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Microglia–vascular interactions are present in the brain from early development into adulthood, through which microglia regulate blood–brain barrier (BBB) permeability, leukocyte extravasation, and angiogenesis ( Dudvarski Stankovic et al, 2016 ; Jolivel et al, 2015 ; Lou et al, 2016 ). In fact, microglia and microglial processes are closely associated with developing blood vessels in the neuroepithelium or in the ventricular zone, while Pu.1 −/− mice or Csf1 op/op mice that lack microglia and macrophages display impaired angiogenesis in the retina ( Arnold and Betsholtz, 2013 ; Dixon et al, 2021 ; Dudvarski Stankovic et al, 2016 ; Penna et al, 2021 ). In the adult brain, CD206-positive perivascular macrophages (PVMs) remain closely associated with blood vessels, while CD206-negative microglial cell bodies occupy the brain parenchyma isolated by the glia limitans ( Goldmann et al, 2016 ; Kida et al, 1993 ; Ransohoff and Engelhardt, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic and pharmacological inhibition of CX3CR1 abolishes capillary constriction in regions of microglial contact through altered microglial expression of the renin-angiotensin system pathway in the adult retina and this CX3CR1-induced microglial vasoregulation is altered early in diabetic retinopathy. [64] In the developing cerebral cortex, more than 80% of the microglia in the ventricular zone (VZ) contact blood vessels in rats, [45] and more than 40% of the total microglia are associated with vasculature in the mouse frontal cortex just after birth, dropping to less than 20% by P14, and maintained at later ages. [65] A strong association between microglia and blood vessels has also been observed in the developing human brain, reaching 38% at 18-24 weeks of gestation.…”
Section: Contribution Of Microglia To the Formation Of Blood Vesselsmentioning
confidence: 99%
“…The number of cortical vessels descending from the pial plexus increases and are distributed at regular intervals in the cortex. [ 45 ] This primitive blood vessel pattern is formed independent of astrocytes in the telencephalon, because astrocytes are generated from E15 onward (Figure 1B). Blood vessels actively sprout and fuse to form a complex network during the first postnatal week.…”
Section: Blood Vessel Formation Is Supported By Neurons and Glial Cellsmentioning
confidence: 99%
“…Numerous studies in the brain and retina have shown close approximation of microglia with developing vessel tips (Ashwell et al, 1989;Checchin et al, 2006). In fact, studies in the cortex have shown that endothelial cells extend processes that directly contact both neural precursor cells and microglia (Penna et al, 2020). Providing direct evidence of a functional role, loss of microglia in PU.1 mutant mice resulted in reduced blood vessel intersections in the hindbrain (Fantin et al, 2010).…”
Section: Vascular Developmentmentioning
confidence: 99%